Synthesized Yttria Stabilised Zirconia as filler in Proton Exchange Membranes (PEMs) with enhanced stability. (February 2018) - Saccà, Ada; Carbone, Alessandra; Gatto, Irene; Pedicini, Rolando; Passalacqua, Enza
Abstract: Composite membranes based on Perfluorosulphonic Acid (PSFA) represent a possible solution to operate at temperatures over 100 °C and low relative humidity ( RH ) levels in Polymer Electrolyte Fuel Cells (PEFCs). Yttria Stabilised Zirconia (YSZ) containing an 8 mol.% of yttrium oxide was synthesised and used to obtain Nafion ® membranes with a variable content of YSZ (3, 5, 10 wt%). The membranes were characterised in terms of XRD, Ion Exchange Capacity ( IEC ), water uptake and swelling at different temperatures (room T, 80 and 95 °C). Proton conductivity, single cell tests in H2 /air ( I-V curves) and Accelerated Degradation Tests (ADTs) were conducted at 120 °C 75% RH . The composite membrane containing a 5 wt% of synthesized YSZ (NsynYSZ5) had the best performance and the highest electrochemical stability, reaching 48 cycles against to 28 cycles of a pristine Nafion membrane. Highlights: Composite membranes based on Yttria Stabilised Zirconia (YSZ) as a filler for PEFCs application at Tcell ≥120 °C. High proton conductivity for synYSZ membranes at Tcell  = 120 °C (75%RH). Higher power density for NsynYSZ5 than pristine membrane. Higher duration for membrane with YSZ 5wt% (@120 °C, 75%RH) than reference during accelerated degradation tests (ADT). An enhanced stability during ADT for the membrane containing a 5 wt% of YSZ (@120 °C, 75%RH) was obtained.